Framework Study for Agile Software Development Via Scrum and Kanban - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
This paper provides a systematic comparison between two well-known Agile methodologies: Scrum, which is a framework of doing projects by allocating tasks into small stages called sprints, and Kanban, which is a scheduling system to manage the flow of work by means of visual signals. In this regard, both methodologies were reviewed to explore similarities and differences between them. Then, a focus group survey was performed to specify the preferable methodology for product development according to various parameters in the project environment including project complexity, level of uncertainty, and work size with consideration of output factors like quality, productivity, and delivery. Results show the flexibility of both methodologies in approaching Agile objectives, where Scrum emphasizes on the corporation of the customer and development teams with a focus on particular skills such as planning, organization, presentation, and reviewing which makes it ideal for new and complex projects where a regular involvement of the customer is required, whereas Kanban is more operative in continuous-flow environments with a steady approach toward a system improvement.
Keywords: Agile software development; Scrum; Kanban; software development life cycle; project management